Implementation of Independent Character Education in Forming a Discussion Culture in Grade VII Students of SMP Bhayangkari Rantau Prapat - Harahap, Ahmad Ariansyah Wafi; Anjar, Agus; Junita, Junita (Jurnal Riset Ilmu Pendidikan, 2024)
The purpose of this study was to determine the implementation of independent character education in Forming a Discussion Culture in Grade VII Students of Bhayangkari Rantau Prapat Middle School. This study uses a qualitative method with a case study approach, focusing on an in-depth understanding of events and problems. Data were obtained from interviews with informants, observations and various document documentation data, while data analysis and triangulation were used to ensure the validity of the information collected. The results of this study indicate that independent character in Forming a Discussion Culture in Grade VII Students of Bhayangkari Rantau Prapat Middle School has a significant impact on the formation of a discussion culture in the classroom. Although there are several challenges in the implementation of independent character education, such as students' lack of self-confidence and dependence on teachers, the efforts made by the school have shown positive results. With the right strategies, such as giving assignments that encourage independence, providing positive feedback, and strengthening the role of peers, a productive discussion culture can be formed among students